SALINITY EFFECTS ON CULTURAL HERITAGE SITES WITH FOCUS ON THE TOMB OF THE KINGS IN PAPHOS - CYPRUS - Dimitriou, Christodoulos; Abate, Dante; Themistocleous, Kyriacos; Eliades, Marinos; Hadjimitsis, Diofantos G. (My University, 2024)
The impact of salt is a process that accelerates the degradation of historical sites or buildings, posing a major problem for coastal sites. Cyprus, an island rich in cultural heritage, experiences significant effects on its sites from sea salinity, as its eastern Mediterranean location is one of the most saline environments in the world. This paper focuses on a preliminary investigation into the effects of salinity on cultural heritage sites, specifically the Tomb of the Kings, located on the southwest coast of Paphos, Cyprus, near the seashore and sea spray. The Tomb of the Kings, a UNESCO World Heritage site, consists of underground monumental burial structures carved out of solid rock, dating from the 4th century BCE to the 3rd century CE. The methodology used to measure the site's salinity levels includes both micro and macro approach, with in situ measurements, laboratory analysis, and remote sensing techniques to correlate and cross validate the results. The main purpose of this study is to create a salinity risk assessment framework, able to analyze how this phenomenon can affect the coastal heritage sites. Preliminary results have highlighted areas of higher and lower concentration of salts at the site, but further investigation is necessary to fully understand the behavior of salinity and its links to the degradation and conservation of the site of Tomb of the Kings.
Keywords: Remote Sensing; Satellite; Salinity; Conductivity; Acidity; Cultural Heritage